PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - Jolin Jolin; Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research is to determine the effect of profitability (ROA), liquidity (CR), firm size (SIZE), and asset structure (AS) on capital structure (DER) in property and real estate companies listed on the Indonesia Stock Exchange for the periode 2019-2021 using a sample of 107 companies selected through purposive sampling to obtain valid data. Processing sample data using the Statistical Package for the Social Sciences version 26. The result of the F test, the result of this study indicate that ROA, CR, SIZE, and AS simultaneously have significant effect on DER. The result of the T test show that ROA and CR have a negative and significant impact on DER. Meantime, SIZE and AS have a positive and significant impact on DER.